Menara Umno, Pulau Pinang / Mohd Khaizuran Aqil Naharuddin ... [et al.] - Naharuddin, Mohd Khaizuran Aqil; Muhd Naim, Muhammad Ridhzuan; Mohd Suhaimi, Mohammad Fakhrul Rizal; Mazlan, Muhd Najmuddin; Wan Abdul Majid, Wan Nurul Shahida (2015)
This study was designed to see how to managing a high rise building. Our project study located at Menara UMNO, Pulau Pinang. It related between theory learned in the class and actual work on the construction site. This study is to identify building background and process in managing the maintenance work in building. Maintenance work was organized by Jawatankuasa Penyertaan Bumiputera (JKPSB) and being responsible to manage about maintenance in building. As they are new at this building, their maintenance policy and planning are not ready in their maintenance organization and they use fully outsource. For in-house, they use civil work maintenance. Building design also related with our project study where their design was show as Tunku Abdul Rahman pose during Independence Day. Condition assessment of the building is synonym as our study before this and we assigned to do survey to this building. From our observation, building condition still in good condition because there were renovations being done. For contract agreement, our building has three tenancies which are from Agensi anti-Dadah Kebangsaan (AADK), UMNO office and Majlis Agama Islam Pulau Pinang (MAIPP). For fire safety system, it is complete with their requirement and needed in building. Financial management is including with our assignment project which is show us how to manage finance in every aspect in building. As a conclusion, problem that has in this building is minor such as preparing in tender for maintenance policy. Although financial and legal aspects are private and confidential for this building, they try to get information from their CEO and finally fulfill our request.